PUBLIC SERVICE ANALYSIS ON IMPROVING COMMUNITY SATISFACTION - Kadir, Haris Abd; Rajindra, Rajindra (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2018)
The purpose of this study to determine the Public Service Against Increasing Public Satisfaction At the District Office Palolo Sigi District. The research used is survey research. The study was conducted in the District Office of Palolo Sigi Regency in 2014. The study population is the entire number of mandatory citizens of ID card in Palolo Subdistrict Sigi Regency as many as 14.016 people, and the sample of 100 respondents with sampling technique proportionate stratified random sampling. The result of the research shows that public service to increase the satisfaction of society, it can be said satisfactory and effective for public satisfaction, and Public Service to Improving Satisfaction of Public at District Office of Palolo Kabupaten Sigi can be said satisfactory, because between the feeling and expectation of society as user of service and value accepted society to the service satisfy the people.Â